The Role of the Working Mother in Preschoolers’ Play Activities - Mariana, .; Boyoh, Debilly Yuan (KnE Life Sciences, 2021)
A key preschooler activity is playtime. When the children play, assistance is needed. The role of mothers in children’s development is very important, particularly with regards to the provision of appropriate games based on the child’s age. However, this is more difficult for working mothers as their time and ability to monitor their children’s development is more limited. This study aims to determine the role of working mothers with regards to play assistance and game selection in pre-school children. The study used a quantitative correlation design. The population and sample in this study were 81 mothers working in the Bandung Advent Hospital with pre-school age children (3-6 years), and a purposive sampling method was used. Data collection consisted of a questionnaire with 12 statements for the assistance element and 10 statements for the game choice element. The data was analyzed by using univariate and bevariat analysis. The findings demonstrate that the role of mothers in children playing assistance is adequate and they generally choose games that are suitable for pre-school age children (72.8%). Moreover, there was no significant relationship between the role of working mothers in play-assistance and choosing toys in pre-school children with pValue> 0.05. Keywords: Role of working mothers, pre-school age children, play accompaniment